Implementation of Election-Level Simplification in Legal Perspective to Overcome Waste of Election Resources and Costs - Yulian Gunhar; Zudan Arief Fakrulloh (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study aims to analyze the implementation of election-level simplification from a legal perspective to overcome the waste of election resources and costs. Elections in Indonesia have faced various challenges, including waste in excessive paper usage, overlapping stages, and inefficient budget allocations. These inefficiencies not only burden the General Elections Commission (KPU) but also affect the effectiveness and transparency of the democratic process. Simplification of election levels is expected to be an effective solution to reduce the administrative and material burdens that hinder the implementation of elections. By streamlining the structure and reducing redundant stages, election organizers can focus more on quality, security, and public participation. This study uses a normative juridical approach by analyzing relevant laws and regulations, such as Law Number 7 of 2017 concerning General Elections, as well as various policies and proposals related to election-level simplification. The analysis also includes legal principles such as efficiency, effectiveness, and legal certainty. Furthermore, the study examines how other democratic countries manage election logistics efficiently to draw lessons that can be contextualized in Indonesia. The results of this study are expected to provide concrete policy recommendations that support the implementation of simplified election systems. These recommendations are aimed at optimizing the election process by minimizing waste, both in terms of budget and the use of natural and human resources, while maintaining the integrity and legitimacy of the democratic process. Thus, this study contributes to the discourse on election reform and democratic strengthening in Indonesia.